Model Asesmen Holistik dalam Pembelajaran PAI berbasis Multiple Intelligence - Suryatina, Zakiya Very Ayu; Muslih, Moh.; Rokhmah, Asnalia (Universitas Nusantara PGRI Kediri, 2026)
Islamic Education (PAI) is confronted with a persistent challenge arising from the misalignment between its holistic aim of nurturing insān kāmil (the complete human being) and assessment practices that remain predominantly cognitive and reductive in nature. As a result, existing assessments have yet to adequately capture students’ character formation, attitudes, and diverse potentials. This study seeks to formulate and develop a holistic assessment model for PAI grounded in Multiple Intelligence theory. Employing a qualitative approach, the research is based on conceptual inquiry and critical analysis of scholarly literature on authentic assessment, Islamic education, and Multiple Intelligence theory. Data were analyzed using a descriptive–analytical technique through the synthesis of key concepts and the systematic mapping of relationships between PAI learning domains and Multiple Intelligence. The findings demonstrate that the integration of Multiple Intelligence theory into PAI assessment can generate a comprehensive, operational, and learner-centered assessment framework, enabling a more equitable and meaningful evaluation of learning outcomes across cognitive, affective, and psychomotor domains. The proposed model offers a humanistic alternative to conventional assessment practices and aligns closely with the philosophical foundations of Islamic Religious Education as well as the demands of 21st-century education.